2014
DOI: 10.1124/dmd.114.061614
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Transporter Proteomics by Liquid Chromatography with Tandem Mass Spectrometry: Addressing Methodologic Issues of Plasma Membrane Isolation and Expression-Activity Relationship

Abstract: To predict transporter-mediated drug disposition using physiologically based pharmacokinetic models, one approach is to measure transport activity and relate it to protein expression levels in cell lines (overexpressing the transporter) and then scale these to via in vitro to in vivo extrapolation (IVIVE). This approach makes two major assumptions. First, that the expression of the transporter is predominantly in the plasma membrane. Second, that there is a linear correlation between expression level and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 13 publications
2
38
0
Order By: Relevance
“…It is suggested, therefore, that the interpretation of the heterogeneity noted in the current analysis cannot be attributed solely to true biologic variability in OATP expression without any additional studies with respect to consistency of proteomic LC-MS/MS methodologies and cross-laboratory comparisons of abundance data using the same biologic samples. A recent report (Kumar et al, 2014) suggested that normalization of absolute abundance levels of OATPs with the abundance of the membrane protein marker Na/K-ATPase can reduce the effect of variability introduced by technical and analytical procedures. The authors demonstrated strong linear correlation between normalized OATP1B1 abundance and uptake of estradiol 17-b glucuronide in vitro, supporting further this concept.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested, therefore, that the interpretation of the heterogeneity noted in the current analysis cannot be attributed solely to true biologic variability in OATP expression without any additional studies with respect to consistency of proteomic LC-MS/MS methodologies and cross-laboratory comparisons of abundance data using the same biologic samples. A recent report (Kumar et al, 2014) suggested that normalization of absolute abundance levels of OATPs with the abundance of the membrane protein marker Na/K-ATPase can reduce the effect of variability introduced by technical and analytical procedures. The authors demonstrated strong linear correlation between normalized OATP1B1 abundance and uptake of estradiol 17-b glucuronide in vitro, supporting further this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Because a blank biologic sample matrix was not available to generate a standard curve, the heavy labeled peptides were used as internal standards to overcome any ion suppression effect produced by the matrix. We have used this approach numerous times to quantify transporter expression in the human liver (Deo et al, 2012;Prasad et al, 2013Prasad et al, , 2016Prasad and Unadkat, 2014a,b;Kumar et al, 2015). In those studies, we used human liver tissue preparation, spiked with known concentrations of peptides, as quality control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Although MATE2-K and breast cancer resistance protein (BCRP) were detected in the cortex, they were below the lower limit of quantification (LLOQ) (signal to noise ratio , 5). Compared with the human liver (Deo et al, 2012;Prasad et al, , 2016Kumar et al, 2015), P-gp and MATE1 expression in the kidney cortex was 2-fold and 10-fold higher than the liver and multidrug resistance protein 2 (MRP2) expression was 2-fold lower than the liver, respectively. Of the transporters quantified, the protein expression showed moderate variability with a percent coefficient of variation of 34%-51% except for MRP4, which was the most variable transporter with a percent coefficient of variation of 70.7%.…”
Section: Comparison Of Transporter Expression In Cortex Samplesmentioning
confidence: 99%
“…Third, our expression data are for total cellular membrane and not purified plasma membrane. However, as we have shown, routine high-throughput isolation of the latter is not possible (Kumar et al, 2014). Therefore, we propose that if the expression of the transporter in plasma membrane versus that in total membrane is similar in liver tissue and in transfected cell lines (expressing the transporter of interest), in vitro-in vivo extrapolation and allometric scaling of transporter-mediated disposition of drugs are valid and should be possible.…”
Section: Interspecies Variability In Hepatobiliary Transporters Exprementioning
confidence: 99%